2010
DOI: 10.5194/bg-7-2711-2010
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas balances of managed peatlands in the Nordic countries – present knowledge and gaps

Abstract: Abstract. This article provides an overview of the effects of land-use on the fluxes of carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O) and from peatlands in the Nordic countries based on the field data from about 100 studies. In addition, this review aims to identify the gaps in the present knowledge on the greenhouse gas (GHG) balances associated with the land-use of these northern ecosystems. Northern peatlands have accumulated, as peat, a vast amount of carbon from the atmosphere since th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
245
9
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 257 publications
(285 citation statements)
references
References 134 publications
28
245
9
3
Order By: Relevance
“…Maljanen et al (2010), in a review of GHG balances for organic soils in the Nordic countries, reported emissions from perennial grasslands to be 0.32 ± 0.64 g CH 4 m −2 (n = 11), which is comparable to the 0.47 g CH 4 m −2 of this study. Similarly, for N 2 O the average emission observed at grassland sites on peat in previous studies in Nordic countries was 1.50 ± 1.60 g N 2 O m −2 (n = 12), a range that includes the average emission of 0.5 g N 2 O m −2 of the present study (Table 8).…”
Section: Ghg Balance Of the Eight Monitoring Sitessupporting
confidence: 75%
See 4 more Smart Citations
“…Maljanen et al (2010), in a review of GHG balances for organic soils in the Nordic countries, reported emissions from perennial grasslands to be 0.32 ± 0.64 g CH 4 m −2 (n = 11), which is comparable to the 0.47 g CH 4 m −2 of this study. Similarly, for N 2 O the average emission observed at grassland sites on peat in previous studies in Nordic countries was 1.50 ± 1.60 g N 2 O m −2 (n = 12), a range that includes the average emission of 0.5 g N 2 O m −2 of the present study (Table 8).…”
Section: Ghg Balance Of the Eight Monitoring Sitessupporting
confidence: 75%
“…Similarly, for N 2 O the average emission observed at grassland sites on peat in previous studies in Nordic countries was 1.50 ± 1.60 g N 2 O m −2 (n = 12), a range that includes the average emission of 0.5 g N 2 O m −2 of the present study (Table 8). For barley an average flux of CH 4 of −0.03 ± 0.18 g m −2 (n = 5) was reported (Maljanen et al, 2010), the range and lower level relative to permanent grasslands was confirmed by the present study. Finally, N 2 O emission factors for barley grown on peat soil were reported to average 1.7 ± 0.5 g m −2 (n = 5), with one study of a potato field in the same range; these values are also comparable to the 2.5 g N 2 O m −2 determined in the present study.…”
Section: Ghg Balance Of the Eight Monitoring Sitessupporting
confidence: 75%
See 3 more Smart Citations